Choice of playing roles of the central defenders on the basis of the analysis of the structure of the special preparedness of qualified female water polo players - Пилипко, Ольга; Пилипко, Аліна (Slobozhanskyi Herald of Science and Sport, 2019)
Olga Pilipko & Alina Pilipko Purpose: to develop and experimentally substantiate the method of choosing the game role of the central defenders on the basis of the analysis of the indicators of the structure of the special preparedness of qualified female water polo players. Material & Methods: analysis and generalization of literary sources, pedagogical observation, anthropometric and physiological measurements, testing, analysis of the game activities of water polo players using test game protocols, methods of mathematical statistics. The contingent of the surveyed were members of the team of the Kharkiv region on the female water floor. Results: the authors determined the features of the structure of special preparedness of qualified female water polo players who perform functions as central defenders, investigated the relationship between physical development indicators, technical and special swimming training of representatives of this role, developed model characteristics of the most significant parameters of the structure of special preparedness of qualified female water polo players to determine the playing role of the central defenders. Conclusion: the definition of playing roles in women's water polo should be based on a comprehensive analysis of indicators that reflect all aspects of preparedness of qualified female athletes.